Genetic relationship of specialty and quality rice (Oryza sativa L.) grown popularly in Vietnam revealed by simple sequence repeat (SSR) markers - Luong, Tran Thi; Cuc, Luu Minh; Thanh, Nguyen Duc (Academia Journal of Biology, 2013)
The genetic relationship analysis of specialty and quality rice in Vietnam is very important for genetic management, conservation and new varietal identification. In this study, sixty rice varieties were selected for the study with 40 SSR markers. A total of 180 alleles were detected by 33 polymorphic markers with an average of 5.45 per locus. Out of 33 polymorphic loci, 61 rare alleles and 14 unique alleles were identified. These unique alleles could be useful for molecular characterization and DNA fingerprinting of 12 rice varieties. Polymorphic information content (PIC) values ranged from 0.06 to 0.83, with an average of 0.6. Genetic similarity coefficient of 60 studied rice varieties ranged from 0.056 to 0.77. Two varieties Jamin 85 (DS28) and LC93-1 had the lowest genetic similarity coefficient. The highest genetic similarity coefficient was recorded in Q5DB (DS42) and KDDB (DS43). The results of this study provide important informations for the study and development of specialty and high quality rice varieties by traditional methods and molecular technologies.